Pengaruh Struktur Modal,Profitabilitas,Ukuran Perusahan Terhadap Nilai Perusahaan Sektor Industri Pertambangan - Mellya Embun baining; Fitri Ana Siregar; Intan Fazira (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine whether there is an influence of capital structure, profitability and company size on the value of companies in the mining industry sector, coal mining sub-sector listed on the BEI in 2018-2022. After the research data was collected and processed by the author, there are points in this research with the following conclusions: Capital structure (X1) on the value of companies in the mining industry sector (Y). In the prob results, the results show a significant value of 0.0000 < a (0.05) and seen from the t-statistic of 1.863491 > t-table of 1.66256 , based on these results, the probability < of the a and t-count values ​​> t-table, meaning that capital structure influences the value of companies in the mining industry sector. Profitability (X2) on the value of companies in the mining industry sector (Y). In the prob results, a significant value of 0.0369 < a ​​(0.05) was obtained and seen from the t-statistic it was 1.874639 > t-table of 1.66256, based on these significant values, Probability < from a and t-count values ​​> t-table, meaning that Profitability has an effect on the value of companies in the mining industry sector. Company size (X3) on the value of companies in the mining industry sector (Y). In the prob results, a significant value of 0.0479 < a ​​(0.05) was obtained and seen from the t-statistic it was 1.987158 > t-table of 1.66256 , based on the significant value, Probability < from the value of a and t-count > t-table, Company Size means that it influences the value of companies in the mining industry sector